Two-component room temperature curing hand-applied urethane waterproofing composition
The two-component urethane waterproofing material composition, featuring a specific combination of polyisocyanate, polyol, diethyltoluene diamine, and aliphatic secondary polyamines, addresses the challenges of working time and durability in DETDA cross-linked materials, achieving extended usability and enhanced resistance to heat and alkali.
Patent Information
- Application Number
- JP2021079299
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-05-07
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2041-05-07
AI Technical Summary
DETDA cross-linked urethane waterproofing materials face challenges in ensuring sufficient working time, especially in summer conditions, while maintaining adequate heat and alkali resistance for long-term durability.
A two-component room temperature curable urethane waterproofing material composition is developed, using a main agent with an isocyanate group terminal prepolymer made of polyisocyanate and polyol, and a curing agent containing aromatic polyamines and secondary aliphatic polyamines, specifically diethyltoluene diamine and aliphatic secondary polyamines of formula (1), to achieve extended working time and enhanced heat and alkali resistance.
The composition provides sufficient working time throughout the year, while exhibiting excellent heat and alkali resistance, meeting the requirement for a 10-year warranty and surpassing standard deterioration test conditions.
Smart Images

Figure 0007653296000001 
Figure 0007653296000002 
Figure 0007653296000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a two-component, room temperature curing, hand-applied urethane waterproofing material composition that can ensure sufficient pot life throughout the year and has excellent durability. [Background technology]
[0002] Because urethane waterproofing materials are suitable for construction in irregular and narrow areas, they are used in the verandas, balconies, and open corridors of apartment buildings and other collective dwellings, as well as relatively large flat areas on roofs, elevations, parapets, and around frames, regardless of whether they are being built in new construction or renovated.
[0003] General polyurethane waterproofing materials are made by mixing two liquid components in a mixer and then applying them by hand with a trowel, spatula, roller, brush, etc., and require at least 30 minutes of usable time (hereafter referred to as "pot life") after mixing with the mixer. The pot life is generally defined as the time from mixing the two components at 23°C until the viscosity reaches 60,000 mPa s. Two-component room temperature curing urethane waterproofing materials for hand application are generally prepared in two types: one for summer application at 30°C or higher and one for winter application at 5°C or lower, because the outdoor temperature is significantly different between winter and summer application. Waterproofing materials for flat surfaces are designed to have a pot life of 30 minutes or more at the application temperature in each season (to achieve this, the pot life at 23°C must be 55 minutes or more). The longer the pot life, the better in application work, but generally, the longer the pot life, the worse the curing, and the longer the time until workers can stand on the coating film to apply the next process (hereinafter referred to as "applicable time"). In normal work, it is desirable to apply the urethane waterproofing material in the evening and have it ready for application by the next morning, and it is considered preferable to be able to adjust the pot life to within about 17 hours throughout the year.
[0004] Traditionally, two-component room temperature curing hand-applied urethane waterproofing materials were based on an isocyanate-terminated prepolymer made of tolylene diisocyanate and polyoxypropylene polyol, and the active hydrogen in one of the curing agents was a relatively low-reactivity aromatic polyamine, 3,3'-dichloro-4,4'-diaminodiphenylmethane (hereinafter referred to as "MOCA"), which was used as the main component, in combination with a low-reactivity secondary polyol, polyoxypropylene polyol. In addition, lead carboxylate was used as a catalyst to promote the reaction of the low-reactivity polyoxypropylene polyol. If lead carboxylate is not used, the reaction with the polyol is not promoted sufficiently, and the reaction between the isocyanate group of the main agent and moisture progresses, especially in summer, and as a result, the by-product carbon dioxide gas causes foaming and reduces the physical properties. The above waterproofing material is called MOCA crosslinked waterproofing material. MOCA is a highly crystalline and poorly soluble raw material, but it can be dissolved and stabilized to a certain extent in polyoxypropylene polyol, which is used as a hardener, and it becomes a waterproofing material with a pot life suitable for hand application, so it has been used as a general-purpose waterproofing material for a long time.
[0005] However, there are major environmental issues with MOCA cross-linking waterproofing materials. The MOCA used in the hardener is designated as a Class 2 specific chemical substance under the Industrial Safety and Health Act, and because it is used in the hardener at more than the upper limit of 1%, it falls under the Regulations for Prevention of Harm with Specified Chemical Substances (hereinafter referred to as the "Specific Regulations"). MOCA has also been classified as Group 1 (carcinogenic to humans) in the carcinogenicity assessment by the International Agency for Research on Cancer (IARC). Furthermore, the use of lead carboxylate compounds, which are necessary to be used as accelerators, is a material whose use is strictly restricted worldwide and is designated as a Type 1 Specified Chemical Substance under the Law Concerning Reporting, etc. of Releases of Specific Chemical Substances and Promoting Their Management (commonly known as the PRTR Law). As such, from an environmental perspective, the use of these materials should be avoided.
[0006] In recent years, a DETDA crosslinked urethane waterproofing material has been developed, which uses an isocyanate-terminated prepolymer made of tolylene diisocyanate and polyoxypropylene polyol as the base material, similar to the MOCA crosslinked waterproofing material, and uses diethyltoluenediamine (hereinafter referred to as "DETDA"), a highly reactive aromatic polyamine, instead of MOCA as the active hydrogen compound in the curing agent. This method has good low-temperature curing properties because DETDA is highly reactive, but has a major problem in ensuring the usable time in summer. For this reason, a method using a polyol and an organotin compound or / and an imidazole compound having substituents at the 1st and 2nd positions as a curing agent (Patent Document 1), a method using a mildly reactive aromatic secondary polyamine and a polyol in combination as a curing agent (Patent Document 2), a method in which 20 equivalent % to 75 equivalent % of the polyol contained in the base material is a diol, and a mildly reactive aromatic secondary polyamine is used in combination as a curing agent (Patent Document 3), etc. have been proposed.
[0007] DETDA cross-linking waterproofing material does not use the specific chemical substance MOCA as a hardener, and furthermore, it does not use lead carboxylate, so there are no problems with hardening or foaming properties, and it is becoming the mainstream instead of MOCA cross-linking waterproofing material. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] Patent No. 5669813 [Patent Document 2] Patent No. 6213954 [Patent Document 3] Patent No. 6187964 Summary of the Invention [Problem to be solved by the invention]
[0009] When polyols or aromatic secondary amines were used in combination with DETDA crosslinked waterproofing materials to ensure a usable time in summer, durability such as heat resistance and alkali resistance was not necessarily sufficient. In recent years, it has become common for urethane waterproofing materials to be guaranteed for 10 years, and it is necessary to place importance on not only initial performance but also durability performance. The main factors that cause durability are ultraviolet degradation and heat / alkali degradation, but ultraviolet degradation is usually protected by a top coat applied on the urethane waterproofing layer, so it depends largely on the performance of the top coat. On the other hand, heat / alkali degradation depends on the performance of the urethane waterproofing material composition itself, so it is very important in designing urethane waterproofing materials. Regarding heat degradation test conditions, JIS A 6021 specifies that degradation treatment should be performed at 80°C for one week, and regarding alkali degradation test conditions, JIS A 6021 specifies that degradation treatment should be performed at 23°C for one week, but in recent years, when it has become commonplace to require a 10-year warranty, evaluations are performed under more severe degradation test conditions to ensure practical performance. [Means for solving the problem]
[0010] In view of these problems, the inventors have conducted extensive research into DETDA cross-linked waterproofing materials and have discovered that by using a base agent containing an isocyanate-terminated prepolymer consisting of polyisocyanate and polyol, and a curing agent containing an aromatic polyamine and an aliphatic secondary polyamine, it is possible to obtain a two-component, room temperature curing, hand-applied urethane waterproofing material composition which has sufficient pot life throughout the year and has excellent heat and alkali resistance, and has thus completed the present invention. The present invention relates to a two-liquid room temperature curing type hand-applied urethane waterproofing material composition comprising a base material containing an isocyanate group-terminated prepolymer consisting of a polyisocyanate and a polyol, and a curing agent containing an aromatic polyamine and an aliphatic secondary polyamine, wherein the aromatic polyamine contains diethyltoluenediamine and the aliphatic secondary polyamine is represented by the formula (1):
[0011] [ka]
[0012] (In the formula, X is an n-valent cyclic or chain aliphatic hydrocarbon group or a polyoxyalkylene polyamine residue having a number average molecular weight of 25 to 5,000, and R 1 and R 2 are each independently an organic group inactive to an isocyanate group, and n is an integer of 2 or greater. The present invention is characterized in that it contains a compound represented by the formula:
[0013] The present invention includes the following aspects. [1] A two-component room temperature curing hand-applied urethane waterproofing material composition comprising a base material containing an isocyanate-terminated prepolymer consisting of a polyisocyanate and a polyol, and a curing agent containing an aromatic polyamine and an aliphatic secondary polyamine, wherein the aromatic polyamine contains diethyltoluenediamine and the aliphatic secondary polyamine is a compound represented by the formula (1)
[0014] [ka]
[0015] (In the formula, X is an n-valent cyclic or chain aliphatic hydrocarbon group or a polyoxyalkylene polyamine residue having a number average molecular weight of 25 to 5,000, and R 1 and R 2 are each independently an organic group inactive to an isocyanate group, and n is an integer of 2 or greater. The present invention relates to a two-component room temperature curing type hand-applied urethane waterproofing material composition, comprising a compound represented by the formula: [2] The two-component room temperature curing hand-applied urethane waterproofing material composition according to [1], in which 70 equivalent % or more of the aromatic polyamine is diethyltoluenediamine, and the equivalent ratio of the aromatic polyamine to the secondary aliphatic polyamine is 50 / 50 to 98 / 2. [3] The two-component room temperature curing hand-applied urethane waterproofing material composition according to [1] or [2], wherein the polyisocyanate contains isophorone diisocyanate or tolylene diisocyanate. [4] Aliphatic secondary polyamines include N,N'-[methylenebis(cyclohexane-4,1-diyl)]bisaspartic acid tetraethyl, N,N'-(hexane-1,6-diyl)bisaspartic acid tetraethyl, N,N'-(2-methylpentane-1,5-diyl)bisaspartic acid tetrabutyl, N,N'-[methylenebis(3-methylcyclohexane-4,1-diyl)]bisaspartic acid tetraethyl, N,N'-(bis-2-propyl)polypropylene glycol 3 The two-component room temperature curing type hand-applied urethane waterproofing material composition according to any one of [1] to [3], which is at least one member selected from the group consisting of tetraethyl N-O,O'-diylbisaspartate, tetraethyl N,N'-(butane-1,4-diyl)bisaspartate, tetraethyl N,N'-(2,2-dimethylpropane-1,3-diyl)bisaspartate, tetraethyl N,N'-(2,4-dimethylhexane-1,6-diyl)bisaspartate, and mixtures thereof. Effect of the Invention
[0016] The two-component room temperature curing hand-applied urethane waterproofing material of the present invention has a sufficient pot life throughout the year and also has excellent durability such as heat resistance and alkali resistance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] The present invention relates to a two-component room temperature curing type hand-applied urethane waterproofing material composition. Here, the term "two-component" refers to two components: the main agent and the curing agent. The room temperature curing type refers to a composition that has the property of curing at ambient temperature, that is, a type that cures by leaving it in the surrounding natural environment without the need for heat. The hand application type refers to a composition that is applied by hand using a trowel, spatula, roller, brush, etc. The two-component room temperature curing hand-applied urethane waterproofing material composition of the present invention comprises a base material containing an isocyanate group-terminated prepolymer consisting of a polyisocyanate and a polyol, and a curing agent containing an aromatic polyamine and an aliphatic secondary polyamine, wherein the aromatic polyamine contains diethyltoluenediamine and the aliphatic secondary polyamine is represented by the formula (1):
[0018] [ka]
[0019] (In the formula, X is an n-valent cyclic or chain aliphatic hydrocarbon group or a polyoxyalkylene polyamine residue having a number average molecular weight of 25 to 5,000, and R 1 and R 2 are each independently an organic group inactive to an isocyanate group, and n is an integer of 2 or greater. The compound includes a compound represented by the formula:
[0020] (Base material: polyisocyanate) The base agent contains an isocyanate group-terminated prepolymer consisting of a polyisocyanate and a polyol. As the polyisocyanate of the present invention, aromatic polyisocyanates such as tolylene diisocyanate, diphenylmethane diisocyanate, and naphthalene diisocyanate, aliphatic or alicyclic polyisocyanates such as isophorone diisocyanate, hexamethylene diisocyanate, norbornane diisocyanate, hydrogenated xylylene diisocyanate, hydrogenated diphenylmethane diisocyanate, and tetramethyl xylylene diisocyanate, and their derivatives such as dimers, allophanates, biurets, adducts, and isocyanurates can also be used. Among them, isophorone diisocyanate, tolylene diisocyanate, and the like are preferably used because they have relatively low reactivity and can easily secure a pot life. These polyisocyanates may be used alone or in combination of two or more.
[0021] (Main polyol) As the polyol used in the base material, polyols usually used in the base material of urethane waterproofing materials can be used, but in order to obtain a base material with low viscosity and good workability, it is preferable to use polyether-based polyols such as polyoxypropylene polyols and polyoxyethylene polyoxypropylene polyols having a molecular weight of 300 to 8000. In addition, other high molecular weight polyols such as polyester-based polyols can also be used in part. Additionally, short chain polyols such as 1,4-butanediol, 3-methyl-1,5-pentanediol, 1,6-hexanediol, propylene glycol, dipropylene glycol can also be used.
[0022] Regarding the number of functional groups of the polyol used in the base resin, when a polyol or an aromatic secondary amine is used in combination with the curing agent, the heat resistance and alkali resistance tend to decrease, and in order to prevent this phenomenon, it was necessary to use a large amount of polyol with three or more functional groups in the base resin to increase the branching points. However, in the present invention, since an aliphatic secondary polyamine is used as the curing agent, the heat resistance and alkali resistance are significantly improved. As a result, it is no longer necessary to use a large amount of polyol with three or more functional groups in the base resin, and it has become possible to use a large amount of diol, which is advantageous for ensuring the pot life. Therefore, it is preferable that the polyol used in the base resin is more than 60 equivalent % of diol and 40 equivalent % or less of polyol with three or more functional groups, and it is more preferable to use 80 equivalent % or more of diol and 20 equivalent % or less of polyol with three or more functional groups. If the diol is 60 equivalent % or less, it becomes difficult to ensure sufficient pot life and elongation. There is no upper limit on the proportion of diol, but since the use of diol alone tends to result in insufficient heat resistance and alkali resistance, it is preferable to use less than 95 equivalent % of diol and more than 5 equivalent % of trifunctional or higher polyol.
[0023] (Main NCO content) Generally, reducing the NCO content of the base agent is an effective way to ensure pot life, but this can result in problems such as reduced curing properties and reduced durability, such as strength, heat resistance, and alkali resistance, which are required for urethane waterproofing materials. However, since the urethane waterproofing composition of the present invention contains diethyltoluenediamine and aliphatic secondary polyamine as the curing agent, it is possible to ensure the strength and durability required for a urethane waterproofing material even in a region where the NCO content is relatively low. In the present invention, the NCO content of the main agent is preferably in the range of 1.5 to 6.0 mass%, since it is possible to ensure the strength and durability required for a urethane waterproofing material while having a sufficient pot life. From the viewpoint of ensuring the pot life and the workable time, the NCO content is more preferably 1.7 to 5.0 mass%, and most preferably 1.9 to 4.5 mass%. If the NCO content is less than 1.5 mass%, it is difficult to ensure the strength and durability required for a urethane waterproofing material, and if it exceeds 6.0 mass%, it is difficult to ensure the pot life.
[0024] (Main component NCO group / OH group equivalent ratio) The NCO group / OH group equivalent ratio, which is the ratio of isocyanate groups to OH groups of the polyol during production of the base resin used in the present invention, is preferably in the range of 1.5 to 2.5, more preferably 1.6 or more and less than 2.3, and most preferably 1.7 or more and less than 2.1. Incidentally, if the NCO group / OH group equivalent ratio is less than 1.5, the viscosity of the base resin will increase significantly, which is undesirable.
[0025] (Synthesis of the base material) The isocyanate-terminated prepolymer of the present invention can be synthesized by heating and mixing a polyisocyanate and a polyol for about 2 to 12 hours at 60 to 120° C. If the reaction is slow, a general urethane reaction accelerator can be used as necessary.
[0026] (Active hydrogen compounds in hardeners) The curing agent contains an aromatic polyamine and an aliphatic secondary polyamine as an active hydrogen compound. The aromatic polyamine includes diethyltoluenediamine (DETDA). DETDA has isomers such as 3,5-diethyl-2,4-toluenediamine and 3,5-diethyl-2,6-toluenediamine, and any of these isomers may be used, or a mixture of these may be used. For industrial use, for example, Ethacure 100 (2,4-isomer / 2,6-isomer mass ratio 80 / 20) manufactured by Albemarle is available.
[0027] The curing agent may contain an aromatic polyamine other than DETDA. When the curing agent contains an aromatic polyamine other than DETDA, the amount of DETDA is preferably 70 equivalent % or more of the total amount of aromatic polyamine, more preferably 80 equivalent % or more, and even more preferably 90 equivalent % or more. If the amount of DETDA, which is highly cohesive, highly reactive, and liquid and has good solubility, is not 70 equivalent % or more, it is difficult to obtain a waterproofing material with good curing properties and high physical properties. Examples of aromatic polyamines that can be used in combination with DETDA include Curehard (registered trademark) MED (4,4'-methylenebis(2-ethyl-6-methylaniline)) manufactured by Kumiai Chemical Industry Co., Ltd., which has a high reactivity similar to DETDA, Kayahard (registered trademark) AA (4,4'-methylenebis(2-ethylaniline)) manufactured by Nippon Kayaku Co., Ltd., Kayabond (registered trademark) C-300 (4,4'-methylenebis(2,6-diethylaniline)) manufactured by Nippon Kayaku Co., Ltd., and Kayabond (registered trademark) C-400 (4,4'-methylenebis(2,6-diisopropylaniline)) manufactured by Nippon Kayaku Co., Ltd.
[0028] Additionally, low-reactivity aromatic polyamines such as Ethacure 300 (dimethylthiotoluenediamine) manufactured by Albemarle Corporation, Elasmer (registered trademark) 650P (polytetramethylene glycol bis(p-aminobenzoate)) manufactured by Kumiai Chemical Industry Co., Ltd., and Porea (registered trademark) SL-100A (poly(tetramethylene / 3-methyltetramethylene ether) glycol bis(4-aminobenzoate)) manufactured by Kumiai Chemical Industry Co., Ltd. can also be used.
[0029] The curing agent contains an aliphatic secondary polyamine together with an aromatic polyamine as an active hydrogen compound. Aliphatic secondary polyamines are represented by the formula (1)
[0030] [ka]
[0031] (In the formula, X is an n-valent cyclic or chain aliphatic hydrocarbon group or a polyoxyalkylene polyamine residue having a number average molecular weight of 25 to 5,000, and R 1 and R 2 are each independently an organic group inactive to an isocyanate group, and n is an integer of 2 or greater. The compound includes a compound represented by the formula:
[0032] In formula (1), X is an n-valent cyclic or chain aliphatic hydrocarbon group having a number average molecular weight of 25 to 5,000, or a polyoxyalkylene polyamine residue. X is an n-valent group having a number average molecular weight of 25 to 5,000, and the number average molecular weight is preferably 50 to 3,000, and more preferably 100 to 2,000. X is an aliphatic hydrocarbon group or a polyoxyalkylene polyamine residue. The aliphatic hydrocarbon group may be an alicyclic hydrocarbon group, a chain hydrocarbon group, or a group having both an alicyclic portion and a chain portion. The alicyclic hydrocarbon group may have a side chain. The chain hydrocarbon group may be a straight chain hydrocarbon group or a branched hydrocarbon group. X is preferably a divalent aliphatic hydrocarbon group. Examples of the divalent aliphatic hydrocarbon group include alkylene, cycloalkylene, cycloalkylalkylene, alkylcycloalkylene, alkylenebiscycloalkylene, alkylenebis(alkylcycloalkylene), cycloalkylenebisalkylene, etc. Here, alkylene is preferably an alkylene having 1 to 8 carbon atoms, cycloalkylene is preferably a cycloalkylene having 5 to 6 carbon atoms, alkyl is preferably an alkyl having 1 to 8 carbon atoms, and cycloalkyl is preferably a cycloalkyl having 5 to 6 carbon atoms. The polyoxyalkylene polyamine residue refers to a group obtained by removing primary amino groups at both ends from a polyoxyalkylene polyamine. The polyoxyalkylene polyamine residue may have a side chain. The polyoxyalkylene polyamine residue is preferably a polyoxyethylene polyamine residue, a polyoxypropylene polyamine residue, a polyoxybutylene polyamine residue, or a polyoxyethylene polyoxypropylene polyamine residue. The polyoxyalkylene polyamine residue is more preferably -(CH(CH3)-CH2-O) x -CH2-CH(CH3)- (wherein x is an integer from 3 to 6).
[0033] In formula (1), R 1 and R 2 R is each independently an organic group that is inactive to an isocyanate group. 1 and R 2 is preferably alkyl having 1 to 15 carbon atoms, more preferably alkyl having 1 to 8 carbon atoms, further preferably methyl or ethyl, and most preferably ethyl. In formula (1), n is an integer of 2 or more. n is preferably an integer of 2 to 6, more preferably an integer of 2 to 4, and most preferably 2.
[0034] Compounds of formula (1) can be synthesized, for example, by reacting an optionally substituted maleate or fumarate ester with a polyamine.
[0035] Specific examples of the compound represented by formula (1) include, but are not limited to, tetraethyl N,N'-[methylenebis(cyclohexane-4,1-diyl)]bisaspartate, tetraethyl N,N'-(hexane-1,6-diyl)bisaspartate, tetrabutyl N,N'-(2-methylpentane-1,5-diyl)bisaspartate, tetraethyl N,N'-[methylenebis(3-methylcyclohexane-4,1-diyl)]bisaspartate, tetraethyl N,N '-(bis-2-propyl)polypropylene glycol 300-O,O'-diylbisaspartate tetraethyl, N,N'-(butane-1,4-diyl)bisaspartate tetraethyl, N,N'-(2,2-dimethylpropane-1,3-diyl)bisaspartate tetraethyl, N,N'-(2,4-dimethylhexane-1,6-diyl)bisaspartate tetraethyl, and at least one selected from the group consisting of these. Among them, N,N'-[methylenebis(cyclohexane-4,1-diyl)]bisaspartate tetraethyl, N,N'-(2-methylpentane-1,5-diyl)bisaspartate tetrabutyl, and N,N'-[methylenebis(3-methylcyclohexane-4,1-diyl)]bisaspartate tetraethyl are preferred.
[0036] The equivalent ratio of aromatic polyamine to secondary aliphatic polyamine in the curing agent is preferably 50 / 50 to 98 / 2, and more preferably 60 / 40 to 95 / 5. If more than 50 equivalent % of the active hydrogen compound in the curing agent is secondary aliphatic polyamine, the curing time becomes too slow, making it difficult to apply the next day, and if it is less than 2 equivalent %, it is difficult to obtain a waterproofing material with sufficient pot life.
[0037] In addition, polyols can be used as active hydrogen in the curing agent in addition to aromatic polyamines and secondary aliphatic polyamines. Examples of polyols that can be used in combination include polyether polyols, polyester polyols, and alkyl polyols. Among them, polyester polyols are preferred, and polyester polyols with low crystallinity and good hydrolysis resistance obtained by reacting a polyol mainly composed of a diol having a side chain such as MPD (3-methyl-1,5-pentanediol) or MOD (2-methyl-1,8-octanediol) with an aliphatic or alicyclic dicarboxylic acid such as succinic acid, adipic acid, azelaic acid, sebacic acid, tetrahydrophthalic acid (anhydride), or hexahydrophthalic acid (anhydride) are more preferred. Furthermore, low-crystallinity aromatic polyester polyols obtained by reacting a diol having a side chain such as MPD or MOD with an aromatic dicarboxylic acid such as phthalic acid or phthalic anhydride are most preferred because they have excellent hydrolysis resistance and mechanical strength. Specific examples include Kuraray Polyol P-520 (number average molecular weight 500) and Kuraray Polyol P-530 (number average molecular weight 500) manufactured by Kuraray Co., Ltd. Low-crystalline polyester polyols obtained by reacting a diol having a side chain such as MPD or MOD with a mixture of the aliphatic or alicyclic dicarboxylic acid and the aromatic dicarboxylic acid are also preferred. Specific examples include Kuraray Polyol P-1011 (number average molecular weight 1000), Kuraray Polyol P-2011 (number average molecular weight 2000), Kuraray Polyol P-1012 (number average molecular weight 1000), and Kuraray Polyol P-2012 (number average molecular weight 2000), all of which are manufactured by Kuraray Co., Ltd. Also preferred are trifunctional polyester polyols obtained by reacting a diol having a side chain such as MPD or MOD with the aliphatic or alicyclic dicarboxylic acid and trimethylolpropane. Specific examples include Kuraray Polyol F-510 (number average molecular weight 500), Kuraray Polyol F-1010 (number average molecular weight 1000), Kuraray Polyol F-2010 (number average molecular weight 2000), and Kuraray Polyol F-3010 (number average molecular weight 3000), all of which are manufactured by Kuraray Co., Ltd. Polyester polyols such as polycaprolactone diol obtained by ring-opening ε-caprolactone are also preferred. Specific examples include PLACCEL 205U (molecular weight 530), PLACCEL L205AL (molecular weight 500), PLACCEL L212AL (molecular weight 1250), PLACCEL 220EB (molecular weight 2000), and PLACCEL L220AL (molecular weight 2000), all of which are manufactured by Daicel Chemical Industries, Ltd. Polycarbonate polyol, which is a type of polyester polyol, also has excellent hydrolysis resistance and mechanical strength, and therefore, in particular, those composed of the above-mentioned non-crystalline polyols can be preferably used. Specifically, Kuraray Polyol C-590 (number average molecular weight 500), Kuraray Polyol C-1050 (number average molecular weight 1000), Kuraray Polyol C-1070 (number average molecular weight 1000), Kuraray Polyol C-1090 (number average molecular weight 1000), Kuraray Polyol C-2050 (number average molecular weight 2000), Kuraray Polyol C-2050R (number average molecular weight 2000), all manufactured by Kuraray Co., Ltd. ), Kuraray Polyol C-2070 (number average molecular weight 2000), Kuraray Polyol C-2070R (number average molecular weight 2000), Kuraray Polyol C-2090 (number average molecular weight 2000), Kuraray Polyol C-2090R (number average molecular weight 2000), Kuraray Polyol C-3090 (number average molecular weight 3000), Kuraray Polyol C-3090R (number average molecular weight 3000), etc.
[0038] When a polyol is used in combination with the curing agent, the equivalent ratio of polyamine (aromatic primary and aliphatic secondary) / polyol is preferably in the range of 50 / 50 to 100 / 0, and more preferably 60 / 40 to 90 / 10.
[0039] (Base isocyanate / curing agent active hydrogen equivalent ratio) The equivalent ratio of the total isocyanate groups in the base resin to the active hydrogens (amino groups + hydroxyl groups) in the curing agent is preferably in the range of 0.8 to 1.6, more preferably 0.9 to 1.5, and most preferably 0.95 to 1.4. If the base resin isocyanate groups / curing agent active hydrogen equivalent ratio is less than 0.8, the active hydrogen will be in excess, resulting in insufficient molecular weight of the cured product and poor physical properties, while if it exceeds 1.6, the strength and durability will be insufficient and the curing property will also be reduced.
[0040] (Cure accelerator) In the present invention, since the curing agent contains DETDA as an aromatic polyamine, which has high reactivity with isocyanate groups, it is not necessary to use a curing accelerator. However, in situations requiring fast curing, formulations for winter use when the application temperature is low, formulations in which a large amount of polyol is used in the curing agent, or cases in which the base isocyanate / curing agent active hydrogen equivalent ratio is high and it is necessary to promote the reaction between excess isocyanate groups and moisture, a curing accelerator can be used as necessary.
[0041] In the present invention, general polyurethane curing accelerators such as organic acids, organic acid metal salts, acid anhydrides, organic tin compounds, and tertiary amine compounds can be used. Among them, organic tin compound catalysts are preferred because they can improve curing properties without shortening the pot life. Although organic tin compound catalysts can be added to the base agent in advance, it is preferable to add them to the curing agent because there is a risk of impairing the storage stability of the base agent. It is preferable to add 0.0005% by mass or more but less than 0.03% by mass to the curing agent. If 0.03% by mass or more is added, the reaction with water is promoted too much, so the coating film becomes prone to foaming and the heat resistance is reduced, and if less than 0.0005% by mass, the catalytic effect is insufficient.
[0042] Specific examples of organic stannic compounds include dibutyltin oxide, dioctyltin oxide, dibutyltin dilaurate, dibutyltin diacetate, dibutyltin di-2-ethylhexanoate, dioctyltin diacetate, dioctyltin dilaurate, dibutyltin dimercaptide, dibutyltin bisacetylacetonate, dibutyltin oxylaurate, dioctyltin dineodecane, dibutyltin bisbutylmalate, and dioctyltin 2-ethylhexylmalate, with dibutyltin dilaurate, dioctyltin dilaurate, and dibutyltin dimercaptide being particularly preferred.
[0043] In winter formulations, it is preferable to use a tertiary amine catalyst. Among tertiary amine catalysts, imidazole compounds are preferable, and they can provide a non-foaming coating film with good low-temperature curing properties. Among them, imidazole catalysts with substituents at the 1st and 2nd positions are more preferable catalysts that can promote the reaction with DETDA, polyol, and moisture (water) in a well-balanced manner even at low temperatures, and can provide a coating film with high strength and high heat resistance even in winter. Imidazole catalysts with substituents at the 1st and 2nd positions can also be used in combination with organometallic catalysts, and it is preferable to use them in combination with organo-tin (II) compound catalysts, and they can provide a waterproofing material with high physical properties and high heat resistance that has very good curing properties without reducing adhesion to the top coat.
[0044] In addition, imidazole catalysts having substituents at the 1st and 2nd positions tend to shorten the pot life, but they can also be blended as a catalyst for adjusting the hardening throughout the year. Furthermore, they can be added at the construction site as a hardening accelerator added on site throughout the year. Specific examples of imidazole catalysts having substituents at the 1st and 2nd positions include 1,2-dimethylimidazole, 1-isobutyl-2-methylimidazole, 1-benzyl-2-methylimidazole, and 1-benzyl-2-phenylimidazole, with 1,2-dimethylimidazole and 1-isobutyl-2-methylimidazole being preferred, and 1-isobutyl-2-methylimidazole being more preferred because it is liquid at room temperature and easy to handle.
[0045] In addition, the hardener can contain plasticizers, fillers, defoamers, wetting agents, weather resistance agents, and other agents that are normally used in urethane waterproofing materials. By adding a thixotropic agent such as colloidal calcium carbonate, it is possible to create a urethane waterproofing material that can be applied to vertical surfaces.
[0046] (Plasticizer) As the plasticizer used in the present invention, a plasticizer that can be generally blended with urethane resin can be used. Specific examples include phthalates such as diisononyl phthalate (DINP), dioctyl phthalate (DOP), and butyl benzyl phthalate (BBP), aliphatic dibasic acid esters, phosphate esters, trimellitates, sebacic acid esters, epoxy fatty acid esters, glycol esters, animal and vegetable oil-based fatty acid esters, petroleum and mineral oil-based plasticizers, and alkylene oxide polymerization-based plasticizers. Among them, diisononyl phthalate (DINP) and dioctyl phthalate (DOP), which have a flash point of 200°C or higher, are unlikely to cause mass loss over the long term, and are aromatic polyesters that are unlikely to cause hydrolysis, so they can be used preferably. In addition, a solvent can be used in the curing agent, but there is a risk of shrinkage due to volatilization after application and a tendency to make inorganic fillers more likely to settle, which also causes environmental problems, so it is preferable to use it within 5 mass%, and it is more preferable not to use it at all.
[0047] In the present invention, the amount of plasticizer used is preferably 15 to 90 parts by mass, more preferably 20 to 80 parts by mass, per 100 parts by mass of the prepolymer component in the base material, from the viewpoints of ensuring pot life and physical properties. If the amount of plasticizer is less than 15 parts by mass, it is difficult to obtain an economical urethane waterproofing material with sufficient pot life, and if it exceeds 90 parts by mass, it becomes difficult to ensure the strength and durability required for a urethane waterproofing material, and the plasticizer bleeds out rapidly. In principle, the plasticizer is mixed with the hardener, but it can also be mixed in part with the base material.
[0048] (Inorganic filler) In addition, the present invention allows the hardener to be blended with an inorganic filler. Blending with an inorganic filler allows the waterproofing material to be economically superior and versatile. Calcium carbonate is preferred as the inorganic filler. Calcium carbonate has a high economic effect, and at the same time, it has good dispersibility during the hardener production, and even if a large amount is blended, it does not thicken the material much, and it is easy to reduce the sedimentation during storage of the hardener, and it also has a high reinforcing effect in terms of physical properties. There are various types of calcium carbonate, such as heavy calcium carbonate, light calcium carbonate, and surface-treated colloidal calcium carbonate, and any of these calcium carbonates can be used.
[0049] In addition, inorganic fillers such as silica, kaolin, talc, bentonite, aluminum hydroxide, and barium hydroxide can be used in part. The inorganic fillers mentioned above contain adhering water, which is thought to react gradually with isocyanate groups, but adhering water is generally not considered to be active hydrogen. It is also generally believed that moisture (water) mixed in when mixing the base agent and the hardener, and moisture (water) absorbed from the coating surface after the waterproofing material is applied, also react to some extent with isocyanate groups.
[0050] In the present invention, by blending a relatively large amount of plasticizer on the hardener side, it is possible to blend a large amount of inorganic filler, and thus the blending ratio of the base agent / hardener can be 1 / 2 (mass ratio), which makes it possible to obtain a waterproofing material that is economical and versatile, and that sufficiently meets the strength and durability required for urethane waterproofing materials while ensuring the usable time. It is preferable to blend the inorganic filler at 20 to 80 mass% based on the total amount of the hardener. If it is less than 20 mass%, the reinforcing effect is insufficient and the economy is impaired, and if it exceeds 80 mass%, the viscosity increases and the workability deteriorates.
[0051] (Other additives) In addition, additives such as wetting agents, antifoaming agents, pigments, weather resistance agents, etc. may be blended in appropriate amounts with the curing agent as required.
[0052] (Base / hardener mix ratio) The compounding ratio of the base agent to the curing agent is not particularly limited, but is preferably in the range of 1 / 1 to 1 / 3, and more preferably 1 / 1 to 1 / 2, in terms of mass ratio.
[0053] (Waterproofing method) In addition, the two-liquid room temperature curing hand-applied urethane waterproofing material of the present invention cannot be applied directly to inorganic substrates such as concrete. In the case of inorganic substrates, the urethane waterproofing material does not adhere to the inorganic substrate, so it can be applied after applying a primer that can block moisture from the substrate to a certain extent and ensure adhesion. In addition, including during renovation, an intermediate primer can be applied on the existing urethane waterproofing layer in some cases. In addition, it can be applied to the inorganic substrate after fixing a breathable buffer sheet, a polymeric sheet such as a PVC sheet, a rubber sheet, or a nonwoven fabric sheet with a primer, adhesive, mechanical fixing, or laying. Furthermore, in the case of a metal substrate, the adhesion cannot be ensured even if the urethane waterproofing material of the present invention is applied directly, so it can be applied after applying a dedicated primer. The present invention is not intended to repair asphalt-based waterproof layers, but is intended to waterproof and protect inorganic substrates such as concrete, metal substrates, polymeric resin substrates, and rubber substrates. In addition, the two-component room temperature curing hand-applied urethane waterproofing material of the present invention requires, as a rule, a top coat to be applied when used in areas exposed to direct sunlight.
[0054] In the present invention, taking practical durability into consideration, durability was evaluated under test conditions stricter than the deterioration treatment conditions specified in JIS A 6021. Specifically, in accordance with JIS A 6021, deterioration treatment was performed at 80°C for 4 weeks (1 week in JIS A 6021) for heat treatment and at 60°C for 1 week (23°C in JIS A 6021) for alkali treatment. As a highly durable waterproof material that fully guarantees a 10-year warranty, it is preferable that the tensile strength ratio after heat treatment under the above conditions is 90% or more, the elongation at break is 400% or more, the tensile strength ratio after alkali treatment is 75% or more, and the elongation at break is 400% or more, and more preferably the tensile strength ratio after heat treatment is 95% or more, the elongation at break is 400% or more, the tensile strength ratio after alkali treatment is 80% or more, and the elongation at break is 400% or more. EXAMPLES
[0055] [raw materials] The raw materials used in the following examples and comparative examples are as follows. [Isocyanate] IPDI: VESTANAT® IPDI, isophorone diisocyanate alone, NCO content 37.8% by mass, NCO functionality approx. 2.0, manufactured by Evonik Japan Co., Ltd. Coronate (registered trademark) T-80: a mixture of 2,4-tolylene diisocyanate / 2,6-tolylene diisocyanate = 80 / 20 (mass ratio), NCO content 48.3 mass%, manufactured by Tosoh Corporation [Base polyol] Sannix (registered trademark) PP-2000: polyoxypropylene diol, average molecular weight 2000, OH value 56.1 mgKOH / g, manufactured by Sanyo Chemical Industries, Ltd. Sannix (registered trademark) PP-400: polyoxypropylene diol, average molecular weight 400, OH value 280.5 mgKOH / g, manufactured by Sanyo Chemical Industries, Ltd. Sannix (registered trademark) GA-3000: polyoxypropylene triol, average molecular weight 3000, OH value: 56.1 mgKOH / g, manufactured by Sanyo Chemical Industries, Ltd. 〔solvent〕 MC-2000 Solvent: Petroleum-based hydrocarbon solvent, normal paraffin, isoparaffin mixture, manufactured by Sankyo Chemical Co., Ltd. [Polyamine] DETDA: Ethacure 100, diethyltoluenediamine, a mixture of 2,4-diamino-3,5-diethyltoluene / 2,6-diamino-3,5-diethyltoluene=80 / 20 (mass ratio), aromatic primary diamine, manufactured by Albemarle Corporation Ethacure 420: 4,4′-methylenebis(N-sec-butylaniline), aromatic secondary diamine, manufactured by Albemarle Corporation Desmophen® NH1220: N,N′-(2-methylpentane-1,5-diyl)bisaspartate tetrabutyl, an aliphatic secondary diamine, manufactured by Covestro Desmophen® NH1420: N,N′-[methylenebis(cyclohexane-4,1-diyl)]bisaspartic acid tetraethyl ester, an aliphatic secondary diamine, manufactured by Covestro Desmophen® NH1520: N,N′-[methylenebis(3-methylcyclohexane-4,1-diyl)]bisaspartic acid tetraethyl ester, an aliphatic secondary diamine, manufactured by Covestro [Curing agent polyol] Kuraray Polyol P-530: Aromatic polyester diol obtained by reacting 3-methyl-1,5-pentanediol with isophthalic acid, average molecular weight 500, OH value: 224.4 mgKOH / g, manufactured by Kuraray Co., Ltd. [Plasticizer] DINP: SansoCizer (registered trademark) DINP, diisononyl phthalate, manufactured by New Japan Chemical Co., Ltd. 〔catalyst〕 Dioctyltin dilaurate: KS-1200A-1, manufactured by Kyodo Pharmaceutical Co., Ltd. NC-IM: 1-isobutyl-2-methylimidazole, manufactured by Air Products Japan Co., Ltd. [Inorganic filler] Calcium carbonate: NS#100, manufactured by Nitto Funka Kogyo Co., Ltd. Additives: Kusumoto Chemicals Co., Ltd.
[0056] [Preparation of base agent] A four-neck flask was charged with a polyol, a solvent, and a catalyst, and then a polyisocyanate, according to the formulations in Tables 1 to 4. The mixture was then reacted at 90 to 100° C. for 2 to 8 hours with stirring to obtain a base resin.
[0057] [Preparation of hardener] According to the formulations in Tables 1 to 4, liquids were charged into a polypropylene container and mixed uniformly at low speed with a stirrer (dissolver blade), after which calcium carbonate was added and mixed at 1500 rpm for 10 minutes to obtain a curing agent.
[0058] [Examples 1 to 3] In Examples 1 to 3, the base agent and the curing agent were obtained according to the formulations in Table 1. The base agent and the curing agent were mixed in a mass ratio of 1:2 to obtain urethane waterproofing material compositions. Example 1, which used Coronate (registered trademark) T-80 as the base polyisocyanate, DETDA as the aromatic polyamine for the curing agent, Kuraray Polyol P-530 as the polyol, and Desmophen (registered trademark) NH1420 as the aliphatic secondary polyamine, had a sufficiently long pot life of 71 minutes at 23°C, and the workable time at 23°C was within 17 hours, allowing work to be done the next day. Furthermore, all of the resulting coating films showed good initial physical properties and sufficiently high heat and alkali resistance as high-elongation hand-applied urethane waterproofing materials. Examples 2 and 3, which were carried out in the same manner as Example 1 except that Desmophen (registered trademark) NH1220 and Desmophen (registered trademark) NH1520 were used as the aliphatic secondary polyamines, had sufficiently long pot lives of 63 and 75 minutes, respectively, and the workable time at 23°C was within 17 hours, allowing work to be done the next day. Furthermore, all of the coatings obtained showed good initial physical properties and sufficiently high heat and alkali resistance as highly elongated hand-applied urethane waterproofing materials.
[0059] [Comparative Example 1] In Comparative Example 1, a base agent and a curing agent were prepared according to the formulation in Table 1. The base agent and the curing agent were mixed in a mass ratio of 1:2 to obtain a urethane waterproofing material composition. Comparative Example 1, which used only DETDA and Kuraray Polyol P-530 without using an aliphatic secondary polyamine as the curing agent active hydrogen, had a short pot life of 40 minutes at 23°C, and it was thought that problems would arise in workability during the hot summer months.
[0060] [Comparative Example 2] In Comparative Example 2, a base agent and a curing agent were prepared according to the formulation in Table 1. The base agent and the curing agent were mixed in a mass ratio of 1:2 to obtain a urethane waterproofing material composition. Comparative Example 2 was carried out in the same manner as Example 1, except that Ethacure 420, an aromatic secondary polyamine, was used instead of the aliphatic secondary polyamine as the curing active hydrogen, and the pot life at 23°C was sufficiently long at 73 minutes, and the workable time at 23°C was within 17 hours, allowing work to be done the next day. Furthermore, the resulting coating film showed good initial physical properties as a high-elongation hand-applied urethane waterproofing material, but the tensile strength ratio after heat treatment was 89%, and the tensile strength ratio after alkali treatment was 72%, which was lower than that of the coating using the aliphatic secondary polyamine.
[0061] [Examples 4 and 5] In Examples 4 and 5, the base agent and the curing agent were obtained according to the formulations in Table 2. The base agent and the curing agent were mixed in a mass ratio of 2:3 to obtain urethane waterproofing material compositions. In Example 4, in which IPDI was used as the base polyisocyanate, DETDA was used as the aromatic polyamine in the curing agent, and Desmophen (registered trademark) NH1420 was used as the aliphatic secondary polyamine, the pot life at 23°C was sufficiently long at 65 minutes, and the workable time at 23°C was within 17 hours, so that work could be done the next day. Furthermore, the obtained coating film showed good initial physical properties and sufficiently high heat and alkali resistance as a highly elongated hand-applied urethane waterproofing material. In Example 5, which was carried out in the same manner as Example 4 except that Desmophen (registered trademark) NH1220 was used as the aliphatic secondary polyamine, the pot life at 23°C was sufficiently long at 60 minutes, and the workable time at 23°C was within 17 hours, so that work could be done the next day. Furthermore, the obtained coating film showed good initial physical properties and sufficiently high heat and alkali resistance as a highly elongated hand-applied urethane waterproofing material.
[0062] [Comparative Example 3] In Comparative Example 3, a base agent and a curing agent were obtained according to the formulation in Table 2. The base agent and the curing agent were mixed in a mass ratio of 2:3 to obtain a urethane waterproofing material composition. In Comparative Example 3, in which only DETDA was used without using an aliphatic secondary polyamine as the curing agent active hydrogen, the pot life at 23°C was as short as 49 minutes, and it was thought that problems would arise in workability during the hot summer months.
[0063] [Comparative Example 4] In Comparative Example 4, a base agent and a curing agent were obtained according to the formulation in Table 2. The base agent and the curing agent were mixed in a mass ratio of 2:3 to obtain a urethane waterproofing material composition. Comparative Example 4 was carried out in the same manner as Example 4, except that Ethacure 420, an aromatic secondary polyamine, was used instead of the aliphatic secondary polyamine as the curing active hydrogen. The pot life at 23°C was 63 minutes, which was sufficiently long, and the workable time at 23°C was within 17 hours, allowing work to be done the next day. Furthermore, the resulting coating film showed good initial physical properties as a high-elongation hand-applied urethane waterproofing material, but the tensile strength ratio after alkali treatment was 65%, which was lower alkali resistance than that of the one using the aliphatic secondary polyamine.
[0064] [Examples 6 to 8] In Example 6, a base agent and a curing agent were obtained according to the formulation in Table 3. The base agent and the curing agent were mixed in a mass ratio of 2:3 to obtain a urethane waterproofing material composition. Example 6 was carried out in the same manner as Example 4 except that the equivalent ratio of DETDA and aliphatic secondary polyamine in the curing agent was 95 / 5. The pot life at 23°C was 60 minutes, which was sufficiently long, and the workable time at 23°C was within 17 hours, so that work could be carried out the next day. Furthermore, the obtained coating film showed good initial physical properties and sufficiently high heat and alkali resistance as a high-elongation type hand-applied urethane waterproofing material. Examples 7 and 8 were carried out in the same manner as Example 6 except that Desmophen (registered trademark) NH1220 or Desmophen (registered trademark) NH1520 was used as the aliphatic secondary polyamine. The pot life at 23°C was 59 minutes and 61 minutes, which was sufficiently long, and the workable time at 23°C was within 17 hours in both cases, so that work could be carried out the next day. Furthermore, the obtained coating film showed good initial physical properties and sufficiently high heat and alkali resistance as a high-elongation type hand-applied urethane waterproofing material.
[0065] [Examples 9 to 11] In Examples 9 to 11, the base agent and the curing agent were obtained according to the formulations in Table 4. The base agent and the curing agent were mixed in a mass ratio of 2:3 to obtain urethane waterproofing material compositions. Examples 9 to 11 were carried out in the same manner as Examples 6 to 8, except that the equivalent ratio of DETDA to secondary aliphatic polyamine in the curing agent was 80 / 20. The pot life at 23°C was 77 minutes, 63 minutes, and 79 minutes, respectively, which was sufficiently long, and the workable time at 23°C was all within 17 hours, allowing work to be done the next day. Furthermore, the resulting coating films all showed good initial physical properties and sufficiently high heat and alkali resistance as high-elongation hand-applied urethane waterproofing materials.
[0066] The measurement methods for each evaluation item are as follows.
[0067] [NCO (mass%)] Weigh out about 1 g of the base material into a 200 mL Erlenmeyer flask, add 10 mL of 0.5 N di-n-butylamine (toluene solution), 10 mL of toluene, and an appropriate amount of bromphenol blue, dissolve it, and then add about 100 mL of methanol. Titrate this mixture with 0.25 N hydrochloric acid solution. NCO (mass%) is calculated using the following formula. NCO (mass%) = (blank titration value - 0.5N hydrochloric acid solution titration value) x 4.202 x 0.25N hydrochloric acid solution factor x 0.25 ÷ sample mass
[0068] [Pot life (minutes)] In an air-circulating environmental test room at 23°C and 50% humidity, the base agent and hardener were mixed in a specified ratio and the time from the start of stirring until the viscosity reached 60,000 mPa·s at 2 rpm using a BH type viscometer was measured (a rough guideline for summer mixes is 50 minutes or more).
[0069] [Workable time (hardening)] In an air-circulating environmental test room at 23℃ or 5℃ and 50% humidity, the waterproofing material was mixed with the base agent and hardener at a specified ratio and applied at 2kg / m 2 After application, the time until it was possible to walk on the coating film with shoes even though it was not completely cured and the next work process could be started was measured, and work within 17 hours was deemed ready for the next day (indicated by ◯ in the example table).
[0070] [Tensile strength (N / mm 2 )] The test pieces were aged at 23°C and 50% humidity for 7 to 14 days and then measured according to JIS A 6021 (JIS A 6021 tensile strength standard for polyurethane rubber high elongation type is 2.3N / mm 2 (The above.)
[0071] [Elongation at break (%)] The test pieces were cured at 23°C and 50% humidity for 7 to 14 days, and measurements were carried out in accordance with JIS A 6021 (JIS A 6021 specifies that the elongation rate at break for high-elongation polyurethane rubber is 450% or more).
[0072] [Tear strength (N / mm)] The test pieces were cured at 23°C and 50% humidity for 7 to 14 days, and measurements were carried out based on JIS A 6021 (JIS A 6021 urethane rubber high elongation type has a tear strength standard of 14N / mm or more).
[0073] [Tensile strength ratio (%) and elongation at break (%) after heat treatment (heat resistance)] After curing for 7 to 14 days at 23°C and 50% humidity, the test pieces were placed in an 80°C dryer for 28 days (JIS A 6021 requires 7 days at 80°C) and heat-treated, and the tensile strength ratio and elongation at break compared to before treatment were measured in accordance with JIS A 6021. A tensile strength ratio of 90% or more and an elongation at break of 400% or more were considered to be highly durable (JIS A 6021 standard for polyurethane rubber-based high elongation types requires a tensile strength ratio of 80% or more and an elongation at break of 400% or more after 7 days at 80°C).
[0074] [Tensile strength ratio after alkali treatment (%) (alkali resistance)] After curing for 7 to 14 days at 23°C and 50% humidity, the alkali treatment conditions were changed to 60°C and 7 days (JIS A 6021 requires 23°C and 7 days), but the treatment was carried out in accordance with JIS A 6021. The tensile strength ratio and elongation at break compared to before treatment were measured, and a tensile strength ratio of 80% or more and an elongation at break of 400% or more were considered to be highly durable (JIS A 6021 urethane rubber high elongation standard requires a tensile strength ratio of 60% or more and an elongation at break of 400% or more at 23°C and 7 days).
[0075] [Table 1]
[0076] [Table 2]
[0077] [Table 3]
[0078] [Table 4] [Industrial Applicability]
[0079] The two-component room temperature curing hand-applied urethane waterproofing material composition of the present invention can be suitably used as a highly durable waterproofing material for waterproofing layers on the roofs of buildings and on verandas of collective housing such as apartment buildings.
Claims
1. A two-liquid room temperature curing type hand-applied urethane waterproofing material composition comprising a base material containing an isocyanate group-terminated prepolymer consisting of a polyisocyanate and a polyol, and a curing agent containing an aromatic polyamine and an aliphatic secondary polyamine, wherein the aromatic polyamine contains diethyltoluenediamine, and the aliphatic secondary polyamine is a compound represented by the formula (1): 【Chemistry 1】 (In the formula, X is an n-valent cyclic or chain aliphatic hydrocarbon group or a polyoxyalkylene polyamine residue having a number average molecular weight of 25 to 5,000, and R 1 and R 2 are each independently an organic group inactive to an isocyanate group, and n is an integer of 2 or more. The present invention relates to a two-component room temperature curing type hand-applied urethane waterproofing material composition, comprising a compound represented by the formula:
2. The two-component room temperature curing hand-applied urethane waterproofing material composition according to claim 1, wherein 70 equivalent % or more of the aromatic polyamine is diethyltoluenediamine, and the equivalent ratio of the aromatic polyamine to the secondary aliphatic polyamine is 50 / 50 to 98 / 2.
3. 3. The two-component room temperature curing type hand-applied urethane waterproofing material composition according to claim 1 or 2, wherein the polyisocyanate comprises isophorone diisocyanate or tolylene diisocyanate.
4. Aliphatic secondary polyamines include N,N'-[methylenebis(cyclohexane-4,1-diyl)]bisaspartate tetraethyl, N,N'-(hexane-1,6-diyl)bisaspartate tetraethyl, N,N'-(2-methylpentane-1,5-diyl)bisaspartate tetrabutyl, N,N'-[methylenebis(3-methylcyclohexane-4,1-diyl)]bisaspartate tetraethyl, and N,N'-(bis-2-propyl)polypropylene glycol 300. The two-component room temperature curing hand-applied urethane waterproofing material composition according to any one of claims 1 to 3, which is at least one selected from the group consisting of tetraethyl-O,O'-diylbisaspartate, tetraethyl N,N'-(butane-1,4-diyl)bisaspartate, tetraethyl N,N'-(2,2-dimethylpropane-1,3-diyl)bisaspartate, tetraethyl N,N'-(2,4-dimethylhexane-1,6-diyl)bisaspartate, and mixtures thereof.
Citation Information
Patent Citations
JP1981069813A
Injection valve
JP1986087964A
Multi-room type air conditioner
JP1987013954A
polyurethane urea elastomer
JP2009513782A
Aliphatic polyurea resin composition and aliphatic polyurea resin
JP2011001397A